Robot-Assisted Laparoscopic Radical Prostatectomy in the Morbidly Obese Patient. (2011) - Yates, Jennifer; Munver, Ravi; Sawczuk, Ihor
Abstract : Introduction . Obesity and prostate cancer are among the more common health issues affecting men in the United States. Methods . We retrospectively reviewed morbidly obese (BMI ≥ 40 kg/m 2 ) patients undergoing RALP between 2004–2009 at our institution. Parameters including operative time, estimated blood loss, hospital stay, pathology, and complication rate were examined. Results . A total of 15 patients were included, with a mean BMI of 43 kg/m 2 . Mean preoperative PSA was 5.78 ng/dL, and Gleason score was 6.6. Mean operative time was 163 minutes, and mean estimated blood loss was 210 mL. The mean hospital stay was 1.3 days. Positive margins were noted in 2 (13%) patients, each with pT3 disease. There were no blood transfusions, open conversions, or Clavien Grade II or higher complications. Conclusions . In our experience, RALP is feasible in morbidly obese patients. We noted several challenges in this patient population which were overcome with modification of technique and experience.